Penguatan Peran Lingkungan Kerja dan Budaya Organisasi dalam Mengoptimalkan Kinerja Dosen Universitas Islam Negeri Alauddin Makassar melalui Kepuasan Kerja - Awaluddin, Murtiadi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2018)
This research aims to know and analyze influence of work environment and organizational culture on job satisfaction and performance of lecturers at UIN ALauddin Macassar. This research uses a explanatory research method, and the population is all the lecturers at UIN ALauddin Macassar. Samples in drag with saturated sample method wich are 65 people. Data analysis was done using structural equation model Structural Equation Modeling or (SEM). Results of the analysis show that the work environment and organizational culture influential positive and significant to job satisfaction and performance of lecturers.